Nephrotoxicity of Immune Checkpoint Inhibitors in Single and Combination Therapy—A Systematic and Critical Review - Javier Tascón; Alfredo G. Casanova; Laura Vicente-Vicente; Francisco J. López-Hernández; Ana I. Morales (Biomedicines)
Background/Objectives: Immune checkpoint inhibitors (ICIs) have generated a revolutionary approach in the treatment of cancer, but their effectiveness has been compromised by immune-related adverse events, including renal damage. Although rare, these effects are relevant because they have been related to poor patient prognoses. The objective of this review was to estimate the current incidence of nephrotoxicity in patients treated with single and double ICI therapies. Methods: A total of 1283 potential articles were identified, which were reduced to 50 after applying the exclusion and inclusion criteria. Results: This study reveals the increase in acute kidney injury associated with these drugs in the last decade and shows that, interestingly, combined therapies with ICIs does not lead to an increase in kidney damage compared with anti-CTLA-4. It also suggests that kidney damage could be underdiagnosed when it comes to interstitial nephritis, because definitive evidence requires a renal biopsy. Conclusions: In perspective, these conclusions could guide clinicians in making decisions for therapy personalization and highlight the need to search for new diagnostic systems that are more sensitive and specific to the type of damage and could replace the biopsy.